2013
DOI: 10.1161/atvbaha.113.301273
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Stabilization of Transthyretin, Cerebrovascular Disease, and Life Expectancy

Abstract: Objective-Transthyretin can cause amyloidosis attributable to destabilization of transthyretin tetramers in plasma. We tested the hypothesis that genetic stabilization of transthyretin associates with reduced risk of vascular disease and increased life expectancy. Approach and Results-We included 68 602 participants from 2 prospective studies of the general population. We genotyped for 2 stabilizing genetic variants in the transthyretin gene (TTR), R104H and T119M, and determined the association of genotypes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 41 publications
4
60
0
1
Order By: Relevance
“…The recently renamed WT TTR Amyloidosis—formally called senile systemic amyloidosis (SSA)—results in a cardiomyopathy that affects as much as 15% of the population exceeding 80 years of age 288, 289, 293, 294 . It was recently reported that WT TTR aggregation in and around the vasculature may be a more prominent cause of vascular diseases than previously thought 295 .…”
Section: Figurementioning
confidence: 87%
“…The recently renamed WT TTR Amyloidosis—formally called senile systemic amyloidosis (SSA)—results in a cardiomyopathy that affects as much as 15% of the population exceeding 80 years of age 288, 289, 293, 294 . It was recently reported that WT TTR aggregation in and around the vasculature may be a more prominent cause of vascular diseases than previously thought 295 .…”
Section: Figurementioning
confidence: 87%
“…An epidemiologic study revealed that the population heterozygous for T119M (a TTR mutant with increased tetrameric stability) have decreased risk of cerebrovascular disease and increased life expectancy when compared with noncarriers individuals (101).…”
Section: Cerebral Ischemiamentioning
confidence: 99%
“…8 WT TTR aggregation on blood vessels also appears to play a central role in a variety of vascular diseases. 37 The autosomal dominant familial TTR amyloidoses present as a polyneuropathy [familial amyloid polyneuropathy (FAP) 38 ] and/or a cardiomyopathy (familial amyloid cardiomyopathy 7,39 ), depending on the identity of the TTR mutation the patient has inherited of the >100 disease-linked variants. 40,41 …”
mentioning
confidence: 99%